Penyalahgunaan Inhalen Jenis Lem Aibon dan Dampaknya terhadap Status Gizi di Kota Kendari - Prasetya, Fikki (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2014)
Social facts on glue behavior in the Punk Community in Kendari City have been known, which generally abuse the Aibon type of glue. This study aims to analyze the behavior of Aibon inhaler abuse (ngelem) in the Punk Community in Kendari City and its impact on their nutritional status. This study uses a qualitative design with a case study approach. The informants taken are Punk children in Kendari City, who have been/still actively glue and smoke. The selection of informants was carried out using the Snowball Research Strategies method. Data in the form of information were collected through in-depth interviews with semi-structured and observational techniques. Data analysis was carried out through the stages of data collection, data reduction (emic), interpretation (ethics) and drawing conclusions from the essence of the interview. The results showed that inhaled abuse was more likely to occur in someone who made a living on their own. Adolescents who tend to be loyal to their associations feel comfortable socializing that is not obtained elsewhere and a high sense of solidarity with friends, so they fall into clingy behavior. Men with 10–18 years of age, on average, dropped out of school, and belonged to the lower middle economic class, who had a greater chance of abusing inhalers. The impact on the nutritional status of users is known that active abusers have a poor nutritional status associated with a significant reduction in body weight.